2021
DOI: 10.3390/met11081257
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Process Parameters, Post-Weld Heat Treatment and Peening Effects on Microstructure and Mechanical Performance of Ti–Al Dissimilar Laser Weldings

Abstract: Dissimilar Ti–Al laser weldings are very interesting due to their difficulties in being processed because of the different physical properties of the alloys and the crack formations during cooling and solidification. In this study, the effect of laser offset and defocusing on microstructure, geometry and mechanical properties response of 2 mm thick dissimilar AA6061/Ti-6Al-4V laser welds was analyzed. Moreover, in order to reduce residual stresses, the joints were both heat-treated and mechanically treated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…Katayama et al [ 108 ] continued research [ 17 ] on high-speed laser welding of titanium and aluminum (50 m/min) using a high-speed camera, and a more detailed study using in-situ spectroscopic analysis of plume induced during Al (upper)–Ti (lower) and Ti (upper)–Al (lower) dissimilar welding. Casalino G. et al [ 110 ] continue their studies [ 62 ] in this case, in addition to the offset of the laser beam, “-” defocusing, heat treatment, and ultrasonic peening are used. This allows obtaining the mechanical properties of the joint at the level of 173 MPa and the elongation of 4.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Katayama et al [ 108 ] continued research [ 17 ] on high-speed laser welding of titanium and aluminum (50 m/min) using a high-speed camera, and a more detailed study using in-situ spectroscopic analysis of plume induced during Al (upper)–Ti (lower) and Ti (upper)–Al (lower) dissimilar welding. Casalino G. et al [ 110 ] continue their studies [ 62 ] in this case, in addition to the offset of the laser beam, “-” defocusing, heat treatment, and ultrasonic peening are used. This allows obtaining the mechanical properties of the joint at the level of 173 MPa and the elongation of 4.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The post-processing (mechanical, heat and plasma treatment) of laser welds and parts produced by laser additive manufacturing [17][18][19].…”
Section: Contributionsmentioning
confidence: 99%
“…The effect of laser offset and defocusing on microstructure, geometry, and mechanical property responses of 2 mm-thick dissimilar AA6061/Ti-6Al-4V laser welds were studied in [17]. In order to reduce residual stresses, the joints were both stress relaxation heattreated (at 530 • C for 2 h followed by air cooling) and mechanically treated by ultrasonic peening (for 1 min/side, the diameter of the peening needle was 3 mm, and the vibration frequency was 20 kHz).…”
mentioning
confidence: 99%
“…Studies have shown that an excessive temperature gradient during Ti 2 AlNb alloy welding was prone to cracking and welding defects [11]. Because of the high residual stress during the heat treatment process after welding, the secondary crack will also appear further [12,13]. The mechanical properties of the welded joints between different materials are anticipated to improve thanks to the excellent weldability of TC17 titanium alloy [14,15].…”
Section: Introductionmentioning
confidence: 99%